2021
DOI: 10.1186/s13049-020-00826-6
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital identification of Covid-19: an observational study

Abstract: Background The novel coronavirus disease 2019 (Covid-19) pandemic has affected prehospital care systems across the world, but the prehospital presentation of affected patients and the extent to which prehospital care providers are able to identify them is not well characterized. In this study, we describe the presentation of Covid-19 patients in a Swedish prehospital care system, and asses the predictive value of Covid-19 suspicion as documented by dispatch and ambulance nurses. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Somewhat surprisingly, the oxygen saturation levels did not differ between the patients with and without COVID-19 in this study. Previous pre-hospital studies [ 4 , 20 ] have found lower oxygen saturation levels in all pre-hospital patients with COVID-19 confirmed later on. In our study we had the aim of including all COVID-19 patients and therefore we might have two archetypes of COVID-19 patients in the present study.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Somewhat surprisingly, the oxygen saturation levels did not differ between the patients with and without COVID-19 in this study. Previous pre-hospital studies [ 4 , 20 ] have found lower oxygen saturation levels in all pre-hospital patients with COVID-19 confirmed later on. In our study we had the aim of including all COVID-19 patients and therefore we might have two archetypes of COVID-19 patients in the present study.…”
Section: Discussionmentioning
confidence: 62%
“…The odds of hospital admission increased with increasing respiratory rate (OR 1.196, 95% CI 1.081–1.324, p = 0.001), rapid shallow breathing index (OR 1.023, 95% CI 1.006–1.040, p = 0.009) and dead space percentage of tidal volume (OR 1.091, 95% CI 1.027–1.159 p = 0.005). A higher respiratory rate among hospitalized patients seems logical as there is evidence that increased respiratory rate is a predictor for hospital admissions, ICU admissions and mortality [ 20 23 ]. Higher dead space fraction has also been found in severe COVID-19 [ 24 ] and non COVID-19 related ARDS [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from Sweden found that up to 54% of COVID-19 patients presented with primary symptoms not typical of COVID-19 [ 14 ]. This proportion was markedly higher than in our study (19%) and it may reflect differences how people with non-severe symptoms use emergency services.…”
Section: Discussionmentioning
confidence: 99%
“…All 13 under-triaged patients were 65 year or older and the majority presented with gastro-intestinal or non-specific symptoms. Previous studies have illustrated that up to 50% of SARS-CoV-2 infections can manifest with gastro-intestinal or atypical symptoms [17,18,42] and that these patients arouse the least suspicion for a COVID-19 infection [43]. In a Belgian screening protocol study, atypical symptoms including confusion, repeated falls and altered general state in patients >75 years of age were additionally considered as signs of possible COVID-19 infection [20].…”
Section: Discussionmentioning
confidence: 99%